Yet another star in the Albireo system: the discovery of Albireo Ad - Jack, Dennis; Schröder, Klaus-Peter; Mittag, Marco; Bastian, Ulrich (Astronomy and astrophysics, 2022)
Albireo is a well-known bright visual double star. It is still unclear if the components A and B form a gravitationally bound system. The component Albireo A is itself a binary star. The orbital parameters of the Albireo Aa, Ac system have been determined only recently. Thus, Albireo is still of interest for current research.Aims. We aim to present evidence for the detection of a new member in the Albireo system. Furthermore, we aim to determine the orbital parameters and to find further conclusions for the Albireo system.Methods. We used spectroscopic observations of Albireo A obtained with the TIGRE telescope and determined the radial velocities during a period of over three years. We analyzed the radial velocity curve with RadVel to determine the orbital parameters. In addition, we determined the stellar parameters of Albireo Aa with iSpec. We found clear evidence for yet another star in the Albireo system orbiting Albireo Aa with a period of about P = 371 days. Several alternative explanations for the periodic radial velocity signal could be discarded. The new companion Albireo Ad is a low mass star of about 0.085 M⊙. We conclude that Albireo is a hierarchical multiple star system and remains an interesting object for future observations and studies.
Gesehen am 10.08.2022